2012
DOI: 10.1002/jbmr.1757
|View full text |Cite
|
Sign up to set email alerts
|

Human apolipoprotein E isoforms differentially affect bone mass and turnover in vivo

Abstract: The primary role of apolipoprotein E (apoE) is to mediate the cellular uptake of lipoproteins. However, a new role for apoE as a regulator of bone metabolism in mice has recently been established. In contrast to mice, the human APOE gene is characterized by three common isoforms APOE ε2, ε3 and ε4 that result in different metabolic properties of the apoE isoforms, but it remains controversial whether the APOE polymorphism influences bone traits in humans. To clarify this, we investigated bone phenotypes of apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
1
21
0
2
Order By: Relevance
“…(4,5) Although many association studies have been performed in various populations, and evidence has been sought for an association between ApoE isoforms and bone phenotypes, the results have been conflicting, probably because the studies have been underpowered to detect the very modest effects on bone mineral density (BMD), bone turnover markers, and fracture that would be expected for variants of this type. (6) For example, in some studies, trends were observed for reduced BMD and increased fracture risk in carriers of the ApoE4 allele, (4,7,8) which is the opposite of the results reported by Deickmann and colleagues (1) in mice; however, in other studies, no associations between ApoE alleles and BMD or fractures were observed. (9,10) Moreover, in a recent meta-analysis of genome-wide association studies that involved more than 100,000 subjects, the ApoE locus did not emerge as a significant determinant of BMD or fracture.…”
Section: N This Issue Of the Journal Of Bone And Mineral Researchmentioning
confidence: 71%
See 4 more Smart Citations
“…(4,5) Although many association studies have been performed in various populations, and evidence has been sought for an association between ApoE isoforms and bone phenotypes, the results have been conflicting, probably because the studies have been underpowered to detect the very modest effects on bone mineral density (BMD), bone turnover markers, and fracture that would be expected for variants of this type. (6) For example, in some studies, trends were observed for reduced BMD and increased fracture risk in carriers of the ApoE4 allele, (4,7,8) which is the opposite of the results reported by Deickmann and colleagues (1) in mice; however, in other studies, no associations between ApoE alleles and BMD or fractures were observed. (9,10) Moreover, in a recent meta-analysis of genome-wide association studies that involved more than 100,000 subjects, the ApoE locus did not emerge as a significant determinant of BMD or fracture.…”
Section: N This Issue Of the Journal Of Bone And Mineral Researchmentioning
confidence: 71%
“…(1) The preclinical experiments were performed using genetically engineered mice in which the endogenous coding sequences of ApoE had been replaced with one of the human ApoE2, ApoE3, or ApoE4 isoforms (so called knock-in mice). These three isoforms differ from each other in the amino acid sequence at codons 118 and 158.…”
Section: N This Issue Of the Journal Of Bone And Mineral Researchmentioning
confidence: 99%
See 3 more Smart Citations